2012
DOI: 10.1073/pnas.1202832109
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic stem cells expressing variants of EGFR-specific nanobodies have antitumor effects

Abstract: The deregulation of the epidermal growth factor receptor (EGFR) has a significant role in the progression of tumors. Despite the development of a number of EGFR-targeting agents that can arrest tumor growth, their success in the clinic is limited in several tumor types, particularly in the highly malignant glioblastoma multiforme (GBM). In this study, we generated and characterized EGFRspecific nanobodies (ENb) and imageable and proapoptotic ENb immunoconjugates released from stem cells (SC) to ultimately deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 32 publications
(39 reference statements)
1
78
0
Order By: Relevance
“…by interacting with the binding of ligands to the extracellular domain of the EGFR were established. [13][14][15][16][17] Unfortunately, these therapeutic approaches are frequently compromised by the development of refractory disease, e.g., by increased signaling via a non-targeted member of the ErbB network, receptor transactivation or increased production/release of ligands. [18][19][20][21][22][23][24][25][26] One idea to overcome such a therapeutic resistance is to go for a direct cytolytic approach 27 e.g., T or NK cells genetically modified with chimeric antigen receptors (CARs) directed against EGFR that can destroy EGFR-overexpressing tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…by interacting with the binding of ligands to the extracellular domain of the EGFR were established. [13][14][15][16][17] Unfortunately, these therapeutic approaches are frequently compromised by the development of refractory disease, e.g., by increased signaling via a non-targeted member of the ErbB network, receptor transactivation or increased production/release of ligands. [18][19][20][21][22][23][24][25][26] One idea to overcome such a therapeutic resistance is to go for a direct cytolytic approach 27 e.g., T or NK cells genetically modified with chimeric antigen receptors (CARs) directed against EGFR that can destroy EGFR-overexpressing tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Xenografted mice survived for 51 days upon treatment with control NSC-ENb2 and 80% of mice survived for 80 days after treatment with NSC-ENb2-TRAIL. These findings indicated that tumoritropic NSC-releasing ENb2 inhibited growth of glioblastoma and effectiveness of ENb2-based therapy was markedly improved by NSC-releasing ENb2-TRAIL [28].…”
Section: Proliferative and Antiproliferative Pathways And Their Rolesmentioning
confidence: 65%
“…For example, NSCs expressing variants of EGFR-specific nanobodies reduced glioma growth and invasiveness [14]. NSCs secreting an anti-HER2 antibody inhibited breast cancer growth in vitro and although an anti-tumor effect wasn't shown, migrated successfully to in vivo to breast cancer xenografts [15].…”
Section: Neural Stem Cellsmentioning
confidence: 99%